Emerging cases of Rabies amidst COVID-19 in Pakistan: A new threat? - Kumar, Harendra (Journal of the Pakistan Medical Association, 2022)
Madam, rabies is a deadly virus which is most of the time spread by the bite of the infected animals (1). In Pakistan, it is endemic with infections mainly caused due to dog bite(2).The lack of proper data on infections caused by rabies makes it very difficult to estimate the fatalities. However, it is believed that the deaths caused by rabies in Pakistan is somewhere between 2000 to 5000 every year (2). Moreover, the recent reported cases of rabies pose a grave concern to the struggling health-set-up of Pakistan (3). Furthermore, most of the viral infections share similar clinical symptoms at first. Rabies and COVID-19 cases also share some same clinical symptoms. Few of the same clinical symptoms may include fever, headache, nausea and vomiting (1, 4). It can be very difficult for the health care workers to diagnose and develop a treatment plan for such patients leading to poor prognosis and unfavourable outcomes. Meanwhile, the emergence and increase in cases of new variants of COVID-19 infections is a big challenge for the country. Recently, Pakistan has been reporting more than 4000 daily COVID-19 infections with most of those caused by delta variant of corona virus and therefore experiencing the fourth wave (5). Furthermore, there is a sharp increase in general trend of dog bites in the months from May-Aug, which supports the fact that summer is the month of hosting of most of the infections caused by Rabies. The improper sanitation of most of the cities of Pakistan plays a major role in aggravating different endemics in the region. Lack of awareness, vaccine hesitancy and knowledge gap further exacerbates the prognosis (3). Proper management plan for treating patients with Rabies should be designed by health regulating bodies which will then help in proper diagnosis of rabies patients by health care workers. Vaccine shortage should be addressed in an efficient way and areas where the prevalence of disease is higher should be well-stocked. Government should devise a proper plan with the help of international organizations like WHO to work on strategies which should be effective enough to minimize the emergence of Rabies amidst COVID-19. The hospitals in Pakistan have already been overwhelmed by COVID cases. If proper action is not taken, not only patients with Rabies will be neglected a proper treatment but the risk of mortality, mutation and simultaneous occurrence of both the viral infections will also increase. Continue...